2022
DOI: 10.1590/1517-7076-rmat-2021-45351
|View full text |Cite
|
Sign up to set email alerts
|

Utilização dos testes estatísticos Kruskal-Wallis e Mann-Whitney para avaliação de sistemas de solos reforçados com geotêxteis

Abstract: RESUMO Esta pesquisa teve por objetivo principal avaliar a influência do tipo de geotêxtil de reforço, solo, posição de inserção do reforço geossintético e energia de compactação no comportamento mecânico de solos reforçados com geotêxtil. Esta avaliação foi baseada nos resultados dos ensaios de Resistência à Compressão Não Confinada (RCNC) e de Resistência ao Cisalhamento Direto (τpico). Para a avaliação da influência desses fatores no comportamento mecânico, utilizaram-se testes não-paramétricos, conforme o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Depending on the defined factors and the type of data collected for this quantitative evaluation, the statistical test chosen was Kruskal-Wallis, ideal for analyzing non-parametric data with 3 groups in the independent variable [Almeida et al, 2022]. The hypotheses established for the statistical test in relation to Effectiveness are:…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Depending on the defined factors and the type of data collected for this quantitative evaluation, the statistical test chosen was Kruskal-Wallis, ideal for analyzing non-parametric data with 3 groups in the independent variable [Almeida et al, 2022]. The hypotheses established for the statistical test in relation to Effectiveness are:…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Suppose the p-value is less than or equal to the signi cance level of 0.05. In that case, the null hypothesis is rejected, and it is concluded that the difference between the population medians is statistically signi cant (Almeida et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…MOHAMADI MERSE et al [25] found through large-scale direct shear tests that geotextile-encased granular columns significantly improve the shear strength and stiffness of soft clay, with the improvement being influenced by the aggregate's relative density and the applied normal stress. ALMEIDA et al [26] observed that an increase in compaction energy leads to enhanced contact between geosynthetic materials and soil, thereby augmenting the interface friction force. SANJANA et al [27] studied the interaction between geogrids and steel slag as well as construction and demolition waste through direct shear and pull-out tests, finding that their shear strength and pull-out resistance are higher than that of sand, and successfully predicted the pull-out performance of geogrids using an artificial neural network model.…”
Section: Introductionmentioning
confidence: 99%